Percutaneous mechanical mitral commissurotomy performed with a Cribier's metallic valvulotome. Initial results - Bastos,Maria Dias de Azeredo (2001)
OBJECTIVE: To evaluate the immediate results of percutaneous mechanical mitral commissurotomy. METHODS: Thirty patients underwent percutaneous mechanical mitral commissurotomy performed with a Cribier's metallic valvulotome from 8/11/99 to 2/4/00. Mean age was 30.7 years, and 73.3% were women. With regards to functional class, 63.3% were class III, and 36.7% were class IV. The echocardiographic score had a mean value of 7.5± 1.8. RESULTS: The mitral valve area increased from 0.97±0.15cm² to 2.16±0.50cm² (p>0.0001). The mean diastolic gradient decreased from 17.9±5.0mmHg to 3.2±1.4mmHg. The mean left atrial pressure decreased from 23.6±5.4mmHg to 8.6±3.1mmHg, (p>0.0001). Systolic pressure in the pulmonary artery decreased from 52.7±18.3mmHg to 32.2±7.4mmHg. Twenty-nine cases were successful. One patient developed severe mitral regurgitation. Interatrial septal defect was observed and one patient. One patient had cardiac tamponade due to left ventricular perforation. No deaths occurred. CONCLUSION: This method has proven to be safe and efficient in the treatment of rheumatic mitral stenosis. The potential advantage is that it can be used multiple times after sterilization, which decreases procedural costs significantly.